PENGARUH E-TRUST, E-SATISFACTION, PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, DAN PERCEIVED ENJOYMENT TERHADAP CONTINUANCE INTENTION E-WALLET DI KOTA MAKASSAR: - - Almu Arrif, Rachmat; Candra, Yeki (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
The increasing popularity of e-wallets is a great opportunity for e-wallet provider companies to continue to grow in Indonesia. Continuous use after the initial period of use determines the benefits and continuity of the use of technology in the long term. The purpose of this study is to assess the influence of E-Trust, E-Satisfaction, Perceived Ease Of Use, Perceived Usefulness, and Perceived Enjoyment on the Continuance Intention of E-Wallet in Makassar City. The data analysis in this study used Multiple Linear Regression Analysis and hypothesis tests (t-test, f-test) which were processed with the SPSS v.25 application. The results of this study show that partial E-Trust, E-Satisfaction, Perceived Ease Of Use, and Perceived Usefulness are proven to have a significant influence on the sustainability of the intention to use E-Wallet in Makassar City. Meanwhile, Perceived Enjoyment does not show a significant partial influence on the sustainability of e-wallet intentions. However, overall, all independent variables simultaneously exert a significant influence on the sustainability of e-wallet usage intentions. This study underlines that the success of e-wallet adoption depends not only on technological aspects, but also on psychological factors and user experience